Facilitation Strategies in Online Group Work from the Perspective of Community of Inquiry - Harendita, Monica Ella; Kristianto, Ignatius Indra (Lembaga Penelitian dan Pengabdian kepada Masyarakat, Universitas Negeri Jakarta, 2022)
The COVID-19 pandemic has resulted in disruptions in a number of aspects of our lives, including in language education. Teaching and learning are now done remotely using various online learning platforms and educational technologies. While one of the foci in 21st-century skills is collaboration, how to design and manage group work in online courses remains a challenge for language educators. The Community of Inquiry (CoI) framework, which consists of teaching presence, cognitive presence, and social presence, has been widely employed in designing an effective online course. Thus, through online questionnaires and interviews, this descriptive qualitative research explored the experiences of seven university lecturers from two private universities in Jogjakarta to know how teaching presence was realized in coping with online group work. The results show how the participants have implemented a variety of facilitation strategies to maintain student engagement through different modes of communication, learning models, progress monitoring, and peer feedback. This research is also expected to shed a light on the challenges and strategies taken by lecturers to ensure that collaboration occurs in their classes.